Bengal Water Craft : Boat-Building and Fishing Communities - Varadarajan, Lotika, (Brill | Manohar Publishers & Distributors, 2016)
This is a unique work on the boat building traditions of Bengal. The boats of West Bengal have been influenced on the one hand by the boats of Bihar and on the other by the traditions of Bangladesh. North Bengal follows the ecology of the sub-Himalayan region and the boats of the region illustrate this well. Thirteen chapters describe the typology of different boats found in West Bengal. From raft and dugout, the survey moves to the rich centre of boat building at Balagarh. From here it moves to cargo carriers such as the bhedi. Boats are linked to ecological regions but massive programmes such as the Damodar Valley Corporation changed the pattern of the waters. The remarkable ingenuity of the boat builders is shown in the new boat types such as the Cho_t Šālti, which were developed in conformity with the changes in river flow. Chapter fourteen outlines fishing activities in the Sundarbans area, linking this to boat typology. From the methodological angle the work follows closely the model evolved by George Hornell. All available historical records have been examined. The author has conducted a meticulous survey of existing ethnological sources which are used to fill in the gaps in our knowledge. A map showing the centres where various types of boats are made in West Bengal has also been included. This book therefore ventures into new ground, linking ecology with historical methodology, and is, above all, a singular tribute to the all round artistry of the Bengal boat builder.